A new angle: a teacher's transformation of mathematics teaching practice and engagement in quantitative reasoning. Issue 1 (2nd January 2022) - Johnson, Heather Lynn; Tzur, Ron; Gardner, Amber; Hodkowski, Nicola M.; Lewis, Allyson; McClintock, Evan
ABSTRACT: We present a case study of an elementary teacher, Jen, who transformed her mathematics teaching practice and deepened her conception of angle measure. Employing Teacher Development Experiment methodology, rooted in a constructivist perspective of learning, we analysed sets of pre/post interviews and classroom observations, for two lessons on angle measure, occurring one year apart. In between, Jen participated in a year-long, school-wide professional development intervention, to support teachers' enactment of conceptual mathematics instruction and foster students' multiplicative and fractional reasoning. Jen transformed her vision and rationale for teaching mathematics, her interpretations of students' mathematical knowing, and her view of what constitutes evidence of mathematical learning. In conjunction, she deepened her knowledge of angle measure, engaging in quantitative reasoning and conceptualising angles as quantities. We discuss implications for supporting teachers to transform their mathematics teaching practice via fostering shifts in their goals for instruction and growth in their mathematical understanding.